(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
يناقش البحث قضية تعميم اليورو وما يثيره من التساؤلات في البيئة الاقتصادية الدولية، أبرزها: هل باستطاعته أن يصبح عملة عالمية قوية؟، هل هو مؤهل لذلك؟، كيف ستكون تأثيراته على الاقتصاديات الأوروبية والدولية؟، هل ستنجح هذه العملة في اكتساب ثقة المتعاملين واحترام المستثمرين؟، هل ستنجح في صوغ هوية أوروبية موحّدة، أم أن غياب مثل هذه الهوية سيكون كافياً للقضاء عليها في المهد؟، هل ستشكل منافساً جدياً للدولار أم ترضى بموقعها كعملة عالمية ثانية؟. وما هي منعكسات الصراع بين اليورو والدولار على العلاقات الأوروبية الأمريكية؟... وغيرها من الأسئلة التي سنحاول الإجابة عليها من خلال إلقاء الضوء على بعض ملفات اليورو. The research raises the issue of Euro generalization with the questions created by it in the world economic environment. Questions like: can the Euro become a strong world currency? Is it qualified for that? What’s the effect of Euro on the world economy? Can this currency succeed to win the trust of the transacted and respect the exploiters? Can this currency succeed to create a union European identity, or the absence of this identity will destroy it in the cradle? Can the Euro be a true emulator of the Dollar or will it be as a second world currency? And what are the implications of the Euro-Dollar conflict on the European-American relationship? A lot of questions will be answered by shedding light on some of Euro files.